Long term treatment of pulmonary arterial hypertension with beraprost, an oral prostacyclin analogue. Issue 6 (1st December 2001) - Vizza, C D; Sciomer, S; Morelli, S; Lavalle, C; Di Marzio, P; Padovani, D; Badagliacca, R; Vestri, A R; Naeije, R; Fedele, F
Abstract : OBJECTIVE: To evaluate the effects of one year's treatment with beraprost, an orally active prostacyclin analogue, in patients with severe pulmonary hypertension. PATIENTS: 13 patients with severe pulmonary hypertension. This was primary in nine, thromboembolic in three, and caused by Eisenmenger syndrome in one. METHODS: All patients underwent right heart catheterisation. Mean (SD) right atrial pressure was 5 (3) mm Hg, mean pulmonary artery pressure was 48 (12) mm Hg, cardiac index was 2.6 (0.8) l/min/m 2, and mixed venous oxygen saturation was 68 (7)%. Beraprost was started at the dose of 20 μg three to four times a day (1 μg/kg/day), increasing after one month to 40 μg three to four times a day (2 μg/kg/day), with further increases of 20 μg three to four times a day in case of clinical deterioration. MAIN OUTCOME MEASURES: New York Heart Association (NYHA) functional class, exercise capacity measured by distance walked in six minutes, and systolic pulmonary pressure (by echocardiography) were evaluated at baseline, after one month's treatment, and then every three months for a year. RESULTS: After the first month of treatment, NYHA class decreased from 3.4 (0.7) to 2.9 (0.7) (p < 0.05), the six minute walking distance increased from 213 (64) to 276 (101) m (p < 0.05), and systolic pulmonary artery pressure decreased from 93 (15) to 85 (18) mm Hg (NS). One patient died after 40 days from refractory right heart failure, and another was lost for follow up at six months. The 11 remaining patients had persistent improvements in functional class and exercise capacity and a significant decrease in systolic pulmonary artery pressure in the period from 1–12 months. Side effects were minor. CONCLUSIONS: Oral administration of beraprost may result in long lasting clinical and haemodynamic improvements in patients with severe pulmonary hypertension.